2016
DOI: 10.26719/2016.22.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oro-dental anomalies among schoolchildren in Sana'a city, Yemen

Abstract: Practitioners and policy-makers need information about the relative frequency of dental anomalies among children in their region. This study investigated the prevalence of different oral anomalies among schoolchildren in Sana'a city, Yemen. A sample of 1000 private and public schoolchildren aged 4-12 years were examined by the same examiner using disposable tongue blades. The total prevalence of oral anomalies was 15.1%, most commonly in boys (male:female ratio 3.2:1) aged 7-12 years. The most prevalent dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
4
6
2
1
Order By: Relevance
“…Our study’s prevalence of dental anomalies was 11.2%, similar to the findings from a study conducted in Yemen [ 30 ] but varied from a previous study among the adult population of the Jazan region [ 22 ]. The similarity of the findings can be explained by the proximity of Jazan to the neighboring country, sharing a similar ethnic background between the regions.…”
Section: Discussionsupporting
confidence: 88%
“…Our study’s prevalence of dental anomalies was 11.2%, similar to the findings from a study conducted in Yemen [ 30 ] but varied from a previous study among the adult population of the Jazan region [ 22 ]. The similarity of the findings can be explained by the proximity of Jazan to the neighboring country, sharing a similar ethnic background between the regions.…”
Section: Discussionsupporting
confidence: 88%
“…There were 20 studies included in the data analysis for a total sample size of 85,976 (Amadori, Bardellini, Conti, & Majorana, ; Arendorf & van der Ross, ; Basalamah & Baroudi, ; Bessa, Santos, Aguiar, & do Carmo, ; Garcia‐Pola, Garcia‐Martin, & Gonzalez‐Garcia, ; Kleinman, Swango, & Pindborg, ; Kose, Guven, Ozmen, Akgun, & Altun, ; Majorana et al, ; Mathew, Pai, Sholapurkar, & Vengal, ; Mumcu, Cimilli, Sur, Hayran, & Atalay, ; Parlak et al, ; Pessoa et al, ; dos Santos, Bessa, Aguiar, & do Carmo, ; Shulman, ; Unur, Bektas Kayhan, Altop, Boy Metin, & Keskin, ; Vieira‐Andrade et al, , ; Vučićević Boras et al, ; Yáñez et al, ; Yilmaz et al, ). Overall, the most prevalent conditions were aphthous ulcerations (1.82%), trauma‐associated lesions (1.33%) and herpes simplex virus (HSV)‐associated lesions (1.33%).…”
Section: Resultsmentioning
confidence: 99%
“…Although the incidence differs between primary teeth and permanent teeth, it is suggested that it may be more common in males. Basalamah et al (2016) examined 1000 school children aged 4-12 years looking for oral anomalies and concluded that the total prevalence of oral anomalies was 15.1%, occurring most commonly in boys (male: female ratio 3.2:1) aged 7-12 years [50]. It is possible that not only fused teeth but also other dental anomalies are more common in males.…”
Section: Literature Reviewmentioning
confidence: 99%